For Better or Worse: Friendship Choices and Peer Victimization among Ethnically Diverse Youth in the First Year of Middle School - Echols, Leslie (J Youth Adolesc, 2016)
As children approach early adolescence, the risk of peer victimization often increases. Many children experience some form of peer victimization during this time, but children who experience chronic victimization may be particularly vulnerable to adjustment difficulties. Thus, identifying risk and protective factors associated with chronic victimization continues to be an important area of research. This study examined the effect of change in the victimization of friends on change in children’s own victimization, taking into account the ethnic group representation of children in their classes. Over 3,000 6(th) grade students (52% female; M = 11.33 years) were drawn from 19 middle schools varying in ethnic composition. Friendships were distinguished by type—reciprocal, desired, and undesired—and a novel methodology for measuring ethnic group representation at the individual level was employed. Multilevel modeling indicated that change in friends’ victimization from fall to spring of 6(th) grade had a differential impact on children’s own victimization by friendship type and that the benefits and consequences of change in friends’ victimization were especially pronounced for children in the numerical ethnic majority. The findings underscore the role of friendship choices in peer victimization, even if those choices are not reciprocated, and highlight the unique social risks associated with being in the numerical ethnic majority.